Implementation of Reversion of Burden of Proof in the Case of Labor - Fauzan; Fauzi , Ahmad; Ngadino, Agus (Technium Social Sciences Journal, 2021)
The problem of employee position that weaker than their employer in the employment relationship. If there any dispute based on Law Number 2 of 2004 prevailing civil law proceeding and in the application of the burden of proof based on Article 163 HIR (Herzien Indonesisch Reglement)/283 RBg (Rechtsreglement Buitengewesten)/1865 BW (burgerlijk wetboek voor Indonesie) that the litigant should hold the burden of proof, while to protect the employee, the international labor standard ILO (International Labour Organization) approved the application of reversal burden of proof especially about employment dismissal, discrimination, and freedom of union. The research utilized the descriptive approach of normative juridical supported by the interview of some judges in the industrial relation court environment and was supported by case studies as supporting data, and afterwords the collected data was analyzed in the qualitative method. This research also implements the approach of legal comparation conducted to obtain the implementation of reversal burden of proof in some different country courts. The research concludes that the international labor standard ILO (International Labour Organization) can be implemented in Indonesian industrial relation court to legally protect the employee from illegitimate employment dismissal, discrimination, and labor union busting carried over by the employer. Some of the verdicts from industrial relation courts have implemented the reversal burden of proof. The best point of this research is the invention of the reversal burden of proof model for discrimination cases and union-busting undertaken by employers secretly.